Determination of nickel in vegetable matrices by atomic absorption spectrometry after preconcentration on activated carbon - Yaman, M; Gucer, S (Soc Chimica Italiana, 1998)
An enrichment method has been optimized for the determination of Ni in vegetable samples of food origin. Dry ashing and wet ashing methods have been used for digestion of the samples tested and these two decomposition methods were compared. Nickel was determined by flame atomic absorption spectrometry. For the enrichment procedure, cupferron and oxine were examined as complexing reagents in the pH range 2.0-9.5 and the chelate formed was adsorbed on the activated carbon. The parameters affecting Ni recovery such as amount of cupferron, amount of activated carbon and stirring time were investigated. Interferences were examined and interference from Mg was overcome by this optimized enrichment method. The relative standard deviation was found to be 3 % for the Ni concentration of 80 mu g L-1. Results for the determination of Ni in various vegetables are given.
Keywords: Solvent-Extraction; Enrichment; Vanadium; Cadmium; Copper; Metals; Waters; Cobalt